Mcm2, Geminin, and KI67 define proliferative state and are prognostic markers in renal cell carcinoma. - Dudderidge, T; Stoeber, K; Loddo, M; Atkinson, G; Fanshawe, T; Griffiths, D; Williams, G (2005)
PURPOSE: The origin licensing factors minichromosome maintenance 2 (Mcm2) and Geminin have recently been identified as critical regulators of growth and differentiation. Here we have investigated the regulation of these licensing factors together with Ki67 to further elucidate the cell cycle kinetics of renal cell carcinoma (RCC). Furthermore, we have examined the role of Ki67, Mcm2, and Geminin in disease-free survival after nephrectomy in patients with localized RCC. EXPERIMENTAL DESIGN: Tissue sections from 176 radical nephrectomy specimens were immunohistochemically stained with Mcm2, Geminin, and Ki67 antibodies. Labeling indices (LI) for these markers were compared with clinicopathologic parameters (median follow-up 44 months). RESULTS: In RCC, Mcm2 is expressed at much higher levels than Ki-67 and Geminin, respectively [medians 41.6%, 7.3%, and 3.5% (P < 0.001)] and was most closely linked to tumor grade (P < 0.001). For each marker, Kaplan-Meier survival curves provided strong evidence that increased expression is associated with reduced disease-free survival time (P < 0.001). Additionally, an Mcm2-Ki67 LI identified a unique licensed but nonproliferating population of tumor cells that increased significantly with tumor grade (P = 0.004) and was also of prognostic value (P = 0.01). On multivariate analysis, grade, vascular invasion, capsular invasion, Ki67 LI >12%, and age were found to be independent prognostic markers. CONCLUSIONS: Although Ki67 is identified as an independent prognostic marker, semiquantitative assessment is difficult due to the very low proliferative fraction identified by this marker. In contrast, Mcm2 identifies an increased growth fraction that is closely linked to grade, provides prognostic information, and is amenable to semiquantitative analysis in routine pathologic assessment.